The Sacrificial Ritual and Commissioners to the South Sea God in Tang China - Yuanlin Wang (Religions, 2021)
Previous studies on the Nanhaishen Temple 南海神廟 (Temple of the South Sea God) in Guangzhou in the Tang dynasty focus mainly on the South Sea God as the patron of the Maritime Silk Road, without thoroughly discussing the state ritual and the sacrificial right of the Tang government. This paper illuminates five new points concerning the ritual. First, the sacrificial ritual to the South Sea God developed from the suburban rituals in previous dynasties into both forms of suburban and local rituals, which was also categorized as the medium sacrifice among the three major sacrifices in the state ritual system of the Tang dynasty. Second, the first commissioner who was sent by the central government to perform the sacrificial ritual to the South Sea God was Zhang Jiuling, and henceforth the temporary assignment of court officials to the ceremonies became institutionalized. In the tenth year of Tianbao (751), the South Sea God was entitled Guangliwang 廣利王 (King Guangli), and the commissioner sent on this mission was Zhang Jiuzhang, Zhang Jiuling’s third younger brother, rather than his second younger brother Zhang Jiugao as seen in some records. Third, most of the commissioners were dispatched by the central government in the early Tang, and therefore the sacrifice to the South Sea God was related to the state ritual system; but in the late Tang local officials became dominant in the ritual ceremonies, and thus good harvests and social stability in the Lingnan region became the major concern of the sacrifice. Fourth, the legend that the Buddhist Master Xiujiu 休咎禪師 took over the temple and accepted the South Sea God as his disciple reflected the reciprocity between Buddhism and the South Sea God belief. Last but not the least, the sacrificial ceremonies to the South Sea God established in the Tang dynasty and performed by the officials of both the central and local governments had a significant influence on the ritual in the following dynasties.